Optimalisasi Pelaksanaan Program Kerja Banjar Cerdas Kabupaten Banjar Melalui Beasiswa “Satu Sarjana di Keluarga Dhuafa” - Lola Malihah; Muhammad Yulian Ma’mun (Fakultas Dakwah IAIN Jember, 2022)
This community service activity is a partnership that was initiated in 2019 between the Faculty of Economics and Islamic Business (FEBI) IAI Darussalam Martapura and the Banjar Regency Baznas. One of the Banjar Regency Baznas programs is Banjar Cerdas, that aims to help children from poor families to pursuit their education. The distribution of this aid targets elementary, middle and high school students who are Banjar residents. This program was further developed and has a wider scope after a partnership agreement was signed between Banjar Regency Baznas and FEBI IAI Darussalam Martapura. A new sub-program, “Satu Sarjana di Keluarga Dhuafa” (One Bachelor at Every Poor Family) has emerged from this collaboration as a expansion from Banjar Cerdas program. Final year students who come from poor and unprivileged families are the beneficiaries of this financial assistance. The result of this program is that 6 student beneficiaries has completed their education and graduated in July 2021.